2004
DOI: 10.1093/jn/134.1.143
|View full text |Cite
|
Sign up to set email alerts
|

Soy Protein Enhances the Cholesterol-Lowering Effect of Plant Sterol Esters in Cholesterol-Fed Hamsters

Abstract: This study aimed to investigate whether the combination of plant sterol esters (PSE) with soy protein or soy isoflavones may have extra cholesterol-lowering effects. Male hamsters (n=20/group) were fed diets containing (g/100 g diet) (A) 20 casein (control), (B) 0.24 PSE, (C) 20 intact soy protein (replacing casein), (D) 0.02 soy isoflavones, (E) 0.24 PSE plus 20 soy protein (replacing casein), or (F) 0.24 PSE plus 0.02 soy isoflavones, for 5 wk. All diets contained 0.08 g cholesterol/100 g diet. Compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
55
2
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(72 citation statements)
references
References 36 publications
10
55
2
5
Order By: Relevance
“…Whereas stearic acid-enriched phytosterol esters fed to hamsters at 5% of the diet lowered non-HDL cholesterol [6], our 2.5% PSE treatments did not lower plasma total, non-HDL, or HDL cholesterol. In contrast, hamsters fed a much lower amount (0.24% of the diet) of phytosterol esters made with unsaturated fatty acids (canola oil) exhibited reductions in plasma non-HDL cholesterol [30,31]. We recently reported that phytosterol esters containing unsaturated fatty acids (oleate) are hydrolyzed in vitro to a much greater extent than phytosterol esters containing saturated fatty acids [22], suggesting that hydrolysis and liberation of free sterol may be important factors in decreasing cholesterol absorption and/or plasma non-HDL cholesterol concentration.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Whereas stearic acid-enriched phytosterol esters fed to hamsters at 5% of the diet lowered non-HDL cholesterol [6], our 2.5% PSE treatments did not lower plasma total, non-HDL, or HDL cholesterol. In contrast, hamsters fed a much lower amount (0.24% of the diet) of phytosterol esters made with unsaturated fatty acids (canola oil) exhibited reductions in plasma non-HDL cholesterol [30,31]. We recently reported that phytosterol esters containing unsaturated fatty acids (oleate) are hydrolyzed in vitro to a much greater extent than phytosterol esters containing saturated fatty acids [22], suggesting that hydrolysis and liberation of free sterol may be important factors in decreasing cholesterol absorption and/or plasma non-HDL cholesterol concentration.…”
Section: Discussionmentioning
confidence: 90%
“…When fed PSE at 2.5% of the diet-assuming approximately 5% hydrolysis and the fact that the sterol moiety is 60% of PSE mass-the maximum amount of free phytosterol liberated from hydrolysis would be equivalent to feeding free phytosterol at 0.075% of the diet. In comparison, feeding 0.24% phytosterol esters made with unsaturated fatty acids [30,31], assuming 90% hydrolysis, would be equivalent to feeding free phytosterol at 0.13% of the diet. If cholesterol-lowering efficacy is indeed dependent on the presence of free phytosterol, then our treatment using stearate esters may have had the disadvantage of resisting hydrolysis and limiting the amount of free phytosterol.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary soy isoflavones, including genistein, have received great attention as anti-atherogenic foods due to their lipid-improving effects [15][16][17][18][19], but in vivo and in vitro findings regarding their total and/or LDL cholesterol-lowering effects have been inconsistent [20][21][22][23][24][25]. Some studies report that dietary supplementation with genistein, a strong bioactive soy isoflavone, lowers total and LDL-cholesterol levels [23,24], while others describe no effect of soy isoflavones on the concentration of LDL-cholesterol even when vascular function is improved [25].…”
Section: Introductionmentioning
confidence: 99%
“…In these connections, soy isoflavones have been reported to have a variety of biological activities including estrogenic [32], antioxidative [19], anti-osteoporotic [1] and anticarcinogenic [18] activities. Furthermore, recent clinical trials [2] and animal studies [4,21,33] also showed that dietary soy proteins or ISF reduce the risk factors for cardiovascular diseases, lowering triglyceride, total and low density lipoprotein (LDL) cholesterol levels and increasing the ratio of HDL/LDL cholesterol. However, the reported beneficial health effects were quite variable in different studies and the lack of understanding in the molecular mechanisms by which lipid metabolism is impacted, may contribute a major part to the discrepancies.…”
Section: Introductionmentioning
confidence: 99%